An architectural level design methodology for smart camera applications. (20th July 2009) - Saha, Sankalita; Kianzad, Vida; Schlessman, Jason; Aggarwal, Gaurav; Bhattacharyya, Shuvra; Chellappa, Rama; Wolf, Wayne
Today's embedded computing applications are characterised by increased functionality, and hence increased design complexity and processing requirements. The resulting design spaces are vast and designers are typically able to evaluate only small subsets of solutions due to lack of efficient design tools. In this paper, we propose an architectural level design methodology that provides a means for a comprehensive design space exploration for smart camera applications and enable designers to select higher quality solutions and provides substantial savings on the overall cost of the system. We present efficient, accurate and intuitive models for performance estimation and validate them with experiments.